Biochar Derived from Rice Husk as Effective Adsorbent for the Removal Congo Red and Procion Red MX-5B Dyes - Alfan Wijaya; Nova Yuliasari (Magister Program of Material Science Graduate School of Universitas Sriwijaya, 2023)
Biochar derived from rice husk was successfully prepared with the pyrolysis method. X-Ray Diffraction (XRD), Fourier-transform infrared spectroscopy (FT-IR), Thermogravimetry analysis (TGA), and Brunauer-Emmett-Teller (BET) analysis confirmed biochar. The results indicate that biochar is amorphous carbon. Functional groups on biochar include -OH, C-H, C-O, C=C, and C-O. The surface area of biochar of 72.252 m2/g with a pore size of 3.334 nm which is classified as mesoporous material. Biochar was used as an adsorbent on the congo red (CR) and procion red MX-5B (PR) dyes with adsorption capacities of 42.918 and 84.034 mg/g, respectively. The equilibrium adsorption occurred at 120 minutes. The adsorption isotherm and kinetics both followed the Langmuir isotherm and Pseudo Second Order (PSO), respectively. CR and PR adsorption process using biochar by physisorption and chemisorption with interactions that occur include hydrogen interactions, physical interactions, π-π interactions, and electrostatic interactions.